Sytematic Literature Review (SLR): Analysis of the Role and Behavior of Indonesian Language in Islamic Education - Meylani, Auliya; Budiman, Budiman; Hasibuan, Nisa Hafzhiyah; Serungke, Mayang; Fadillah, Mutia Asmi Asmi; Wety, Elfina (Program Pascasarjana UIN Sumatera Utara, 2024)
The aim of this research is to reveal the role and behavior of the Indonesian language in Islamic education and to find out in-depth results of the patterns and formation of the role and behavior of the Indonesian language in Islamic education. The method used is the Systematic Literature Review (SLR) method. Data is used by collecting journal articles found on Google Scholar, Research Gate, which have been published in the 2016-2023 period. Islamic education is one of the media that can be used in the world of education to develop the character of students. The use of inaccurate language, both vocabulary and sentence structure, causes less information to be conveyed.